Cranial skeletogenesis of one of the largest amphibians, Andrias japonicus, provides insight into ontogenetic adaptations for feeding in salamanders. Issue 1 (8th July 2021) - Ishikawa, Kaoru; Taguchi, Yuki; Kobayashi, Ryomei; Anzai, Wataru; Hayashi, Toshinori; Tokita, Masayoshi
Abstract: Skeletal development in salamanders is greatly influenced by their complex life history. Although the relationship between skull development and life history has been investigated in a variety of salamander species, few studies have compared skull development among lineages. Here, we describe the cranial skeletogenesis of the Japanese giant salamander, Andrias japonicus (family Cryptobranchidae), for the first time. To conduct interspecific comparisons, we also describe the cranial skeletogenesis of Hynobius nebulosus (Hynobiidae), Pleurodeles waltl (Salamandridae) and Ambystoma mexicanum (Ambystomatidae). Our comparative analyses reveal interspecific differences in cranial skeletogenesis, particularly in the timing of the onset of ossification, the direction of ossification (e.g. from anterior to posterior) and the ossification pattern of the hyobranchial skeleton. The early onset of jaw ossification, posterior extension of the maxilla and posterolateral inclination of the squamosal in An. japonicus might be adaptations that allow An. japonicus to gulp feed, primarily using the suction force generated by opening the mouth wide, while also supplementing that force by depressing the hyobranchial skeleton. Multivariate regression of skull shape on log10 -transformed centroid size revealed that the unique skull shape of adult and subadult An. japonicus forms through hypermorphosis.